Mesoporous molecularly imprinted polymer core@shell hybrid silica nanoparticles as adsorbent in microextraction by packed sorbent for multiresidue determination of pesticides in apple juice. (30th May 2021) - Dinali, Laíse Aparecida Fonseca; de Oliveira, Hanna Leijoto; Teixeira, Leila Suleimara; de Souza Borges, Warley; Borges, Keyller Bastos
Graphical abstract: Highlights: Production of a mesoporous MIP synthesized on the surface of silica nanoparticles. Core@mMIP showed excellent selectivity for the pesticides studied in apple juice. Innovative association of the core@mMIP with MEPS for pesticide extraction. New method for pesticides determination based on MEPS and HPLC/UV. Method was validated and successfully applied in real juice samples. Abstract: In this work, we report the synthesis of a mesoporous molecularly imprinted polymer on the surface of silica nanoparticles (core@mMIP) to be applied as adsorbent in microextraction by packed sorbent (MEPS) for selective determination of pesticides in apple juice. The core@mMIP was properly characterized, showing good adhesion of the polymer to the silica core. The best extraction conditions were: 200 µL of ultrapure water as washing solvent, 150 µL of acetonitrile as eluent, 100 µL of sample at pH 2.5, five draw-eject cycles and 8 mg of adsorbent. Thereby, recoveries of 96.12 ± 1.05%, 76.88 ± 6.18% and 76.18 ± 5.57% were obtained for pyriproxyfen (PPX), deltamethrin (DTM) and etofenprox (ETF), respectively. After validation, the method presented linearity in the range of 0.02–10 µg mL −1 (r > 0.99), limit of detection of 0.005 µg mL −1, satisfactory selectivity, and proper precision and accuracy. The method was successfully applied real samples of processed and fresh apple juice.